Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1590/0001-3765202220210765
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of factors related to biofilm formation in Providencia stuartii

Abstract: Providencia stuartii is one of the Enterobacteriaceae species of medical importance commonly associated with urinary infections, which can also cause other ones, including uncommon ones, such as liver abscess and septic vasculitis.This bacterium stands out in the expression of intrinsic and acquired resistance to antimicrobials. Besides, it uses mechanisms such as biofi lm for its persistence in biotic and abiotic environments. This study investigated the cellular hydrophobicity profi le of clinical isolates o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 53 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…It was observed that in Figure 2 it is possible to evidence the formation of biofilm by fluorescence. For this, we used SYBR Green (capable of intercalating in the hydrogen bridges of double strand of bacterial DNA) and Calcofluor White dyes (which binds the β1-6 polysaccharide bonds that are formed in the exopolysaccharide matrix or EPS) [34] [35] [36]. The fluorescence technique is widely used, these dyes together in our work were capable to show the biofilm and prove that Enterococcus isolates can be able to form biofilm in different surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that in Figure 2 it is possible to evidence the formation of biofilm by fluorescence. For this, we used SYBR Green (capable of intercalating in the hydrogen bridges of double strand of bacterial DNA) and Calcofluor White dyes (which binds the β1-6 polysaccharide bonds that are formed in the exopolysaccharide matrix or EPS) [34] [35] [36]. The fluorescence technique is widely used, these dyes together in our work were capable to show the biofilm and prove that Enterococcus isolates can be able to form biofilm in different surfaces.…”
Section: Discussionmentioning
confidence: 99%